Typical Hemolytic Uremic Syndrome with Diffused Brain Ischemia as a Complication: A Case Report of a Child in Iran - Javadi Larijani, Faezeh; Sayarifard, Azadeh; Javadi Larijani, Farnia; Ataei, Nematolla; Pajouhi, Atieh (Journal of Pediatric Nephrology, 2013)
<span style="line-height: 115%; font-family: 'Cambria','serif'; font-size: 10pt; mso-ascii-theme-font: major-latin; mso-hansi-theme-font: major-latin; mso-bidi-font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman';">Hemolytic uremic syndrome includes hemolytic anemia, acute kidney injury, and thrombocytopenia. In this article, a child with hemolytic uremic syndrome (HUS) and acute nervous system involvement is reported. <span style="line-height: 115%; font-family: 'Cambria','serif'; font-size: 10pt; mso-ascii-theme-font: major-latin; mso-hansi-theme-font: major-latin; mso-bidi-font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman';">The patient was a 22-month-old boy who presented with hemorrhagic diarrhea and anuria. He was admitted by the impression of HUS and received supportive care such as acute peritoneal dialysis and packed cell infusion. During recovery period and after the beginning of the fifth session of dialysis, the child suddenly experienced loss of consciousness and focal convulsion in some extremities which led to hemiparesis of the left side of the body, and speech and swallowing impairment. The patient underwent a diagnostic and therapeutic process and was followed for one year. Any organ damage such as nervous system involvement and an appropriate period of follow up should be considered in a typical HUS syndrome, especially in pediatric patients. Keywords:Hemolytic-Uremic Syndrome; Brain Ischemia; Infarction; Child; Iran.